Felinosis: the elusive-cat scratch disease - Arulmozhi, S.; Kumar, Sithananda; Divakaran, Shilpa; Kurian, Susy Sophia; Kurien, Mary (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Cat-scratch disease or felinosis is an infection caused by Bartonella henselae which is characterized by chronic inflammation of the lymph nodes. It is one of the causes of regional, unilateral adenitis in children and adolescents. Axillary lymph nodes followed by cervical, pre-auricular and submandibular lymph nodes are the most common sites of involvement. We report a 14 year old male patient with cat scratch disease in whom the initial clinical manifestations were indistinguishable from those of acute bacterial suppurative lymphadenitis.